Cohesion Policy Meets Heterogeneous Firms - Loredana Fattorini; Mahdi Ghodsi; Armando Rungi (The Vienna Institute for International Economic Studies (wiiw), 2018)
In this paper, we empirically test the effects of the EU's 'cohesion policy' on the performance of 273,500 European manufacturing firms after combining regional policy data at NUTS 2 level with firm-level data. In a framework of heterogeneous firms and different absorptive capacity of regions, we show that the financing of 'cohesion policy' by the European Regional Development Fund (ERDF) aimed at direct investments in R&D correlates with an improvement of firms' productivity in a region. Conversely, funding aimed at overall Business Support correlates with negative productivity growth rates. In both cases, we registered an asymmetric impact along the firms' productivity distribution, where a stronger impact can be detected in the first quartile, i.e. less efficient firms in a region. We finally argue that considering the heterogeneity of firms allows a better assessment of the impact of 'cohesion policy' measures.
Keywords: D22; D24; E23; F15; L25; 330; firm performance; total factor productivity; cross-country analysis; convergence; regional policy